2021
DOI: 10.3390/coatings11060712
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition Based Preparation of Zn–Ni Alloy and Zn–Ni–WC Nano-Composite Coatings for Corrosion-Resistant Applications

Abstract: Zinc (Zn) is one of the five most widely consumed metals in the world. Indeed, more than 50% of all the zinc produced is used in zinc-galvanizing processes to protect steel from corrosion. Zn-based coatings have the potential for use as a corrosion-resistant barrier, but their wider use is restricted due to the poor mechanical properties of Zn that are needed to protect steel and other metals from rusting. The addition of other alloying elements such as Ni (Nickle) and WC (Tungsten Carbide) to Zn coating can i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…Nickel, zirconium, aluminium, molybdenum and chromium, as powder elements, are a good choice for applications that require high toughness with moderate resistance to fretting, erosion and scuffing. Zinc-based coatings are widespread in applications that require increased corrosion resistance, but if this chemical element is not alloyed with other elements such as tungsten carbide or nickel, it has low mechanical characteristics [8]. The degradation of the Zn-polymer interface has been studied by the authors of the paper [9], and they point out that the delamination can be inhibited by CO 2 gas in a humid environment.…”
Section: Introductionmentioning
confidence: 99%
“…Nickel, zirconium, aluminium, molybdenum and chromium, as powder elements, are a good choice for applications that require high toughness with moderate resistance to fretting, erosion and scuffing. Zinc-based coatings are widespread in applications that require increased corrosion resistance, but if this chemical element is not alloyed with other elements such as tungsten carbide or nickel, it has low mechanical characteristics [8]. The degradation of the Zn-polymer interface has been studied by the authors of the paper [9], and they point out that the delamination can be inhibited by CO 2 gas in a humid environment.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results show that the flame retardant nanocoating can be used as a fire-warning sensor. There are varieties of nanocoatings prepared from metal, ceramic, and PNCs capable of protecting the metal surfaces from corrosion [65][66][67][68].…”
Section: Nanocoatingmentioning
confidence: 99%
“…In order to improve the thermal conductivity, diamond surface coating [9][10][11] and metal matrix alloying [12][13][14] have been applied to enhance the interfacial bonding between the diamond and the metal matrix. The surface coating method excels in improving composite performance; Kumar et al developed a series of zinc-based coatings such as Zn-WO 3 [15] and Zn-Ni-WC composite nanocoatings [16], which exhibit excellent corrosion resistance and high hardness, greatly expanding the application of steel in boat structures, manufacturing, nuclear power plants, etc. Studies have shown that the addition of alloying elements can drastically reduce the TC of the magnesium matrix [17].…”
Section: Introductionmentioning
confidence: 99%